ANALYSIS OF THE IMPLEMENTATION OF THE PRUDENTIAL PRINCIPLE IN THE FINANCING OF BA’I BITSAMAN ‘AJIL AT KSPPS GUNA LESTARI JAYA, TROSO BRANCH - Alma'lufah, Robi'ah; Mubarok, Ahmad Fauzan; Utami, Cahyaning Budi (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
Ba'i Bitsaman Ajil financing is financing carried out with a system of buying and selling goods that can be paid in installments that require the application of prudential principles to maintain the stability and sustainability of cooperative finances. The main focus of the study is the evaluation of the application of prudential principles in the process of distributing Ba'i Bitsaman Ajil financing, as well as identifying internal and external obstacles faced. The study used a descriptive qualitative approach with a field study method, involving interviews, observations, and documentation. The results of the study indicate that the implementation of prudential principles in distribution is applied through 5C analysis, verification of non-fictional and guaranteed objects of sale and purchase, restrictions on financing ceilings, and committee meeting mechanisms. However, several obstacles were still found, such as limited human resources, manual administration systems, lack of transparency of borrower finances, unstable economic conditions, risk of bias in the verification process carried out with borrower neighbors, and low legal literacy of members. Therefore, it is necessary to strengthen human resource capacity, digitalization, increase education for members, and economic and social monitoring to optimize the implementation of prudential principles